Surgeon‐performed thyroid ultrasound—proving utility and credibility in selecting patients for fine needle aspiration according to the American thyroid association guidelines. A retrospective study of 500 patients. (25th September 2017) - Cohen, O.; Raz Yarkoni, T.; Lahav, Y.; Azoulay, O.; Halperin, D.; Yehuda, M.
Abstract : Design: Case series with chart review. Setting: Single academic centre. Participants: The data of all patients who underwent surgeon‐performed ultrasound (SUS) between 7/2009 and 9/2012 were retrospectively reviewed. Main outcome measures: A correlation between sonographic features and a non‐benign cytologypathology. Results: Four hundred ninety‐eight nodules were included. Solid texture, irregular margins, hypo‐echogenicity and intranodular vascularity were significantly associated with malignancy when benign to non‐benign cytology was compared, and when compared to malignant pathology. Lack of suspicious features was significantly associated with benign lesions, with a negative predictive value of 94%. Except for taller than wider shape, malignancy odds ratio was significantly higher for known suspicious features, reaching 4.81 for irregular borders (CI 2.42‐9.55, P < .001). Conclusions: SUS has proven to be a reliable and consistent tool to assess the thyroid nodule risk stratification. Surgeons should recognise the potential of this tool and its implementation.